Efeitos in vivo e in vitro da cafeína sobre a diferenciação osteogênica das células tronco mesenquimais e atividade de síntese de osteoblastos e condrócitos de ratos - Amanda Maria Sena Reis (2017)
Caffeine is an active alkaloid that can cause damage to bone tissue and cartilage in formation during prenatal life and into adulthood. This compound is transfered to offspring through the placenta and milk, causing a reduction in the bone formation and growth. The hypothesis of present study is that mesenchymal stem cells (MSCs), osteoblasts and chondrocytes, responsible for originating the skeleton, can be targets of caffeine. To try to elucidate the cellular and molecular mechanisms by which caffeine acts on these cells, four separate experiments were performed. The objective was to evaluate the effect of caffeine on the osteogenic differentiation of MSCs from bone marrow (experiment 1), osteoblast synthesis activity of the calvaria (experiment 2), and chondrocyte synthesis activity (experiment 3), obtained from rat offspring of dams who received 25, 50 and 100mg/Kg of caffeine during pregnancy (experiment 2 and 3) or during pregnancy and lactation (experiment 1). In the fourth experiment, the objective was to evaluate the effect of different concentrations of caffeine, added to the culture medium on chondrocyte synthesis activity extracted from newborn rats. In the first and second experiments, we assessed cell viability, alkaline phosphatase activity, collagen synthesis and mineralized nodules and expression of gene transcripts for osteocalcin, osteopontin, sialoprotein, alkaline phosphatase, collagen I and Runx-2 by qRT-PCR. In the third and fourth experiments, we assessed cell viability and activity of synthesis by cytochemical analysis, morphometric and quantification of gene transcripts for Sox-9, Runx-2, aggrecan, collagen II and alkaline phosphatase by qRT-PCR. The data from the four experiments were analyzed by ANOVA to compare the means by SNK test. Differences were considered significant if p 0.05. In MSCs, doses of 50 and 100 mg/Kg of caffeine reduced the activity of alkaline phosphatase in all periods studied and the expression of collagen I at 21 days. The expression of gene transcripts for alkaline phosphatase, Runx-2 and bone sialoprotein and synthesis of mineralized nodules reduced in all doses of caffeine (experiment 1). Osteoblasts obtained from offspring of rats that received caffeine at a dose of 50mg/Kg during pregnancy showed an increase in gene transcripts synthesis for osteocalcin, osteopontin, sialoprotein, alkaline phosphatase and collagen type 1, resulting in increased synthesis of mineralized nodules (experiment 2). In chondrocyte cultures from all groups treated with caffeine, effects were non-linear or dose-dependent. The chondrocyte cultures obtained from groups treated with the dose of 25 mg/Kg showed the lower values, reducing viability and percentage of cells, alkaline phosphatase activity, collagen synthesis and chondrogenic matrix, as well as the expression of Sox-9, alkaline phosphatase and collagen I. Chondrocyte cultures of group treated with 50 mg/Kg of caffeine decreased collagen synthesis and expression of Sox-9. The dose of 100 mg/Kg reduced the collagen synthesis, as well as the expression of Sox-9 and alkaline phosphatase (experiment 3). In vitro, caffeine reduced significantly and dose-dependent manner the conversion of MTT into formazan, the percentage of cells/field, collagen synthesis, alkaline phosphatase activity and synthesis of chondrogenic matrix PAS +, safranin O +, alcian blue + as well as the expression of gene transcripts for aggrecan, Sox-9 and II collagen (experiment 4). It is concluded that the effects of caffeine vary according to their action in vivo or in vitro, with their concentration or dose and the type of cell in which it is acting. Overall, the in vivo effects of caffeine on stem cells and chondrocytes and the in vitro effect on chondrocytes is negative and harmful, while their in vivo effects on osteoblasts, the same doses tested on MSCs and chondrocytes, are contrary, increasing the viability and synthesis activity of these cells.